CODE-MIXING AS A BILINGUAL INSTRUCTIONAL STRATEGY IN EFL CONTEXT - Marlan, A. Aksa; Xiting, Wang (PEOPLE: International Journal of Social Sciences, 2016)
This research investigated the code-mixing technique from perspectives of teacher and student in university teaching contexts, more specifically the use of L1 (Chinese) in L2 (English) in Chinese university English education programs. Through the analysis of results of semi-structured interview, several themes emerged: (1) from the student’s perspective, the use of code-mixing at classes helps her to understand the lesson better, while she also performed resistance to the overuse of code-mixing; (2) from the perspective of the teacher, the use of code-mixing helps her to address the complex or difficult points more easily to the class; (3) the use of code-mixing influences not only linguistic competence , but also cognitive and sociocultural aspects of the learner. The results demonstrate that using bilingual instruction significantly enhance the way both teacher and student use English.